К разработке основ синтаксиса курдского языка - Хамоян, Максим («Զանգակ - 97»)
For the first time in this article are discussed prior questions of syntax o f the Kurdish language, such as the object and volume of syntax as a science, methods and aspects of investigations of syntactic material, models of formation of syntactic units and some others.
Keywords: Лингвистика; Курдский язык